Design and Optimization of Energy-Efficient VLSI Architectures for AI-Driven Inference on Edge Devices - T.Senthil; R. Prashanth (National Journal of Electrical Electronics and Automation Technologies, 2025)
The MTTThe fact that artificial intelligence (AI) is rapidly growing in edge computing has demanded the design of highly power-efficient VLSI architectures that can execute the inference of AI using a limited power and area budget. This paper represents an attempt to propose and optimize VLSI-based AI-driven edge devices with a specific set of accelerators. This architecture will use the combination of different low-power design strategies on integrating the technique of quantization-aware synthesis, aggressive clock gating and memory access optimization techniques to drastically decrease the level of power consumption without affecting the accuracy of inference. Methodically the architecture was designed in System Verilog and synthesized on a 28nm CMOS technology node. The process of Latency, throughput, and energy investigated trade-off options through High-Level Synthesis (HLS) and RTL-level simulations. This architecture was compared against the following benchmarking models ready to be implemented in the edge setting: MobileNet and ResNet. Measurement of experimental results shows that the proposed VLSI accelerator can attain up to 60 percent less power consumed and a 45 percent improvements in performance-per-watt as traded off against same system that are baseline static. The designed implementation has scored a balanced trade-off in terms of both energy, area, and latency therefore is apt to utilize in edge systems with power restrictions/thermal limits. This paper is part of efforts towards developing scalable and power-conscious AI accelerators, and all the components are ready to be used in the development of next-generation energy-efficient AI-specific edge intelligence modules. Its performance and adaptability position the architecture best when applied to real application in the embedded vision, clever IoT nodes and autonomous edge computing platforms.